Distribution of Atmospheric Stability Classes in Baghdad Province and Its Relationship with Surface Wind Speed Rates - Al-Khuwaylidee, Imad Khraibet Rashid; Hassoon, Ahmed F.; Al-Ramahi, Fouad K. Mashee (Iraqi Journal of Science, 2024)
Stability in the atmosphere is the most important factor in the transport and dispersion of air pollutants. There are a number of complicated methods for determining stability. The majority of these methods are based on the amount of convective and mechanical turbulence in atmospheric motions, such as the Richardson number, Monin-Obukhov length, Pasquill-Gifford stability classification, and Pasquill-Turner stability classification. Pasquill utilized surface-accessible meteorological information like breeze speed, sun-based radiation, and surface darkness to portray air steadiness. Baghdad territory was separated into a gathering of focuses as indicated by scope and longitude; six focuses were chosen and conveyed in a manner that addresses all districts of Baghdad territory through the diurnal hourly information (6, 9, 12, 15, 18) for the months (January, April, July, October) for the year 2018, and find the spatial and fleeting circulation of relative recurrence RF% dependability classes as per consolidating the Pasquill-Turner strategy. The pattern of conditions necessary for atmospheric stability can be derived from two distinct categories. First, the patterns for the month and the season are calculated. The results show that in April, the relative frequency (RF%) of the (A) and (B) classes is highest in the northeast of Baghdad province and has an inverse relationship with average wind speed (R = - 0.62, - 0.90). During July, the relative frequency RF percentages of the (C) and (D) classes are highest in the west and northeast of Baghdad province, respectively, and they are positively correlated with average wind speed (R = 0.91, 0.78, respectively). The spatial and worldly conveyance of relative recurrence RF% steadiness classes as per joining the Pasquill-Turner strategy prompts a feeble relationship or an absence of clarity in the relationship because of the impact of affecting elements (non-direct variety) (the Pasquill-Turner Technique (PTM) in extra factors of the Pasquill strategy). Second, monthly and seasonal patterns are calculated. The Pasquill method reveals that the stability class (C) has the highest relative frequency (RF%) in January (28.72 percent), the stability class (B) has the highest relative frequency (RF%) in April (33.98 percent), the stability class (C) has the highest relative frequency (RF%) in July (64.74 percent), and the stability class (C) has the highest relative frequency (RF%) in October (35.48 percent).